Introduction to Robotics Technology for High School Students in Nganjuk Regency through Line Follower Robot Training - Firdaus, Rohim Aminullah; Meta Yantidewi; Endah Rahmawati; Dzulkiflih; Muhimmatul Khoiro; Nugrahani Primary Putri (Journal of Dedication in Community, 2024)
In the era of rapid technological advancement, mastering robotics has become crucial for the younger generation. A community service program by the Physics Study Program lecturer team of Surabaya State University introduced robotics training to high school students at SMAN 1 Nganjuk. This program aimed to foster interest in science and technology, enhance critical thinking, and develop problem-solving skills. The training included systematic steps such as needs analysis, material preparation, implementation, and evaluation. Students learned to design, assemble, and test line follower robots, integrating theory and hands-on practice to understand robotics concepts and techniques comprehensively. The program's outputs include video documentation, news articles, training modules registered as Intellectual Property Rights (IPR), and scientific articles for national journals. Supported by the Nganjuk Regency Education Office, the program aims to enhance students' technological competencies and inspire greater achievements. It also serves as a model for similar initiatives in other regions, promoting technology education development in Indonesia. Evaluation based on participant questionnaires showed positive results: understanding of material (80%), material relevance (81%), usefulness (83%), instructor quality (87%), facilities (93%), and training time adequacy (83%). Overall, the program achieved very good results, successfully engaging students and meeting its objectives.